Mapping global changes in nuclear cytosine base modifications in the early mouse embryo - Li, Y (Reproduction, 2016)
Reprogramming epigenetic modifications to cytosine is required for normal embryo development. We used improved immunolocalization techniques to simultaneously map global changes in the levels of 5′-methylcytosine (5meC) and 5′-hydroxymethylcytosine (5hmC) in each cell of the embryo from fertilization through the first rounds of cellular differentiation. The male and female pronuclei of the zygote showed similar staining levels, and these remained elevated over the next three cell cycles. The inner cells of the morula showed a progressive reduction in global levels of both 5meC and 5hmC and further losses occurred in the pluripotent inner cell mass (ICM) of the blastocyst. This was accompanied by undetectable levels of DNA methyltransferase of each class in the nuclei of the ICM, while DNA methyltransferase 3B was elevated in the hypermethylated nuclei of the trophectoderm (TE). Segregation of the ICM into hypoblast and epiblast was accompanied by increased levels in the hypoblast compared with the epiblast. Blastocyst outgrowth in vitro is a model for implantation and showed that a demethylated state persisted in the epiblast while the hypoblast had higher levels of both 5meC and 5hmC staining. The high levels of 5meC and 5hmC evident in the TE persisted in trophoblast and trophoblast giant cells after attachment of the blastocyst to the substratum in vitro. This study shows that global cytosine hypomethylation and hypohydroxymethylation accompanied the formation of the pluripotent ICM and this persisted into the epiblast after blastocyst outgrowth, and each differentiated lineage formed in the early embryo showed higher global levels of 5meC and 5hmC.